2017
DOI: 10.3390/su9111957
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Effect of Corporate Environmental Performance on Corporate Financial Performance in Developed and Developing Countries

Abstract: Abstract:The relationship between corporate environmental performance and corporate financial performance has been extensively studied in developed countries, and has received less attention in developing countries. For this reason, the main objective of this paper is to examine the effect of corporate environmental performance on corporate financial performance during a global financial crisis, depending on the economic development level of the country where a firm is located. To this end, we obtain data for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
124
1
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(174 citation statements)
references
References 135 publications
15
124
1
5
Order By: Relevance
“…Moreover, our literature review confirmed the statement of Manrique and Martí-Ballester [30] (p. 1), that the relationship between corporate environmental performance and corporate financial performance has been extensively studied in developed countries, and has received less attention in developing countries, in particular with respect to the banking sector. To our knowledge, this kind of studies is almost in-existent.…”
Section: Csp-cfp Relation In Banks and Its Determinants In Ceecsupporting
confidence: 58%
See 2 more Smart Citations
“…Moreover, our literature review confirmed the statement of Manrique and Martí-Ballester [30] (p. 1), that the relationship between corporate environmental performance and corporate financial performance has been extensively studied in developed countries, and has received less attention in developing countries, in particular with respect to the banking sector. To our knowledge, this kind of studies is almost in-existent.…”
Section: Csp-cfp Relation In Banks and Its Determinants In Ceecsupporting
confidence: 58%
“…This approach states that CSR can be strategically managed to add value, sustainability and competitiveness to the company and seeks to foster CFP through CSP [5]. However, the neoclassical economic theory indicates that through the implementation of CSR policy the company's profitability could be decreased as a result of high production costs linked to environmental innovation [30] (p. 21).…”
Section: Heterogeneity Of Relation Between Corporate Social-environmementioning
confidence: 99%
See 1 more Smart Citation
“…However, there are still contradicting ideas on the signs of the relationship between CSR and financial performance. The documented sign of the relationship may indicate negative [3], neutral [4], or positive [5][6][7][8] linkages. Accounting and finance researchers have also documented important findings on the benefits of CSR, such as reduced business risk, information asymmetry, cost of capital, insider trading profit and analyst forecast errors and increased customer trust and loyalty, employee retention, productivity, and company reputation.…”
Section: Introductionmentioning
confidence: 99%
“…According to several studies that analyzed the effect of corporate environmental performance on corporate financial performance conducted by Manrique and Ballester (2017), Soewarno et al 2018, and Dobre et al 2015stated that corporate environmental performance has a significant positive effect on corporate financial performance. Meanwhile, according to research conducted by Iwata and Okada (2010), states that corporate environmental performance has no significant influence on the corporate financial performance.…”
Section: Corporate Environmental Performance and Corporate Financial mentioning
confidence: 99%